Construction of asymptotic representations of solutions from the classL?? for systems of differential equations by the method of characteristic matrix functions - Ivanyuk, N. N. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
For solutions of a system of q-linear n-order differential equations with singularity rank p/r,p,r N. the asymptotic representations are constructed in a sector of the complex plane with a central angle that does not exceed π r/p by using the method of characteristic matrix functions.